Recent Advances in Biotechnologies for the Treatment of Environmental Pollutants Based on Reactive Sulfur Species - Kaili Fan; Wei Wang; Xijun Xu; Yuan Yuan; Nanqi Ren; Duu-Jong Lee; Chuan Chen (MDPI AG, 2023)
The definition of reactive sulfur species (RSS) is inspired by the reactivity and variable chemical valence of sulfur. Sulfur is an essential element for life and is a part of global geochemical cycles. Wastewater treatment bioreactors can be divided into two major categories: sulfur reduction and sulfur oxidation. We review the origins of the definition of RSS and related biotechnological processes in environmental management. Sulfate reduction, sulfide oxidation, and sulfur-based redox reactions are key to driving the coupled global carbon, nitrogen, and sulfur co-cycles. This shows the coupling of the sulfur cycle with the carbon and nitrogen cycles and provides insights into the global material−chemical cycle. We also review the biological classification and RSS metabolic mechanisms of functional microorganisms involved in the biological processes, such as sulfate-reducing and sulfur-oxidizing bacteria. Developments in molecular biology and genomic technologies have allowed us to obtain detailed information on these bacteria. The importance of RSS in environmental technologies requires further consideration.